Taking heat : the president, the press, and my years in the White House - Fleischer, Ari, 1960- (New York : William Morrow, 2005)
The former White House spokesperson shares the leadership lessons he learned under America's first CEO president and discusses such topics as the 2000 election and the inner workings of the White House press corps.
The winds of war -- Austin, Texas -- The early days -- Bias? -- Lester -- The calm before the storm -- September 11, 2001 -- The aftermath -- You'll attack when? -- Anthrax and war -- Fall becomes winter -- Life resumes, Bush knew, Arafat's gone, and the market tumbles -- Helen Thomas -- Is the news accurate? -- Going to the United Nations -- Just one bullet; Election Day, 2002; and the inspections resume -- Groundhog day -- War -- Saying good-bye.
Includes index.
Keywords: Bush, George W. -- 1946- -- Relations with journalists; Bush, George W. -- 1946- -- Friends and associates; Fleischer, Ari, -- 1960-; Presidential press secretaries -- United States -- Biography; United States -- Politics and government -- 2001-2009.; Bush, George W; Fleischer, Ari; Pressestelle